Amphiphilic Marine Antifouling Coatings Based on Zwitterion-Modified Silicone Polymers - Tian, Shu (Langmuir : the ACS journal of surfaces and colloids, 2024)
Silicone coatings are widely employed in marine antifouling applications due to their low surface energy. However, in static marine environments, pure silicone coatings are ineffective in preventing the adhesion of marine biofilms, which consist of proteins, marine bacteria, and extracellular matrices, ultimately promoting the attachment of macrofouling organisms. To address the limitations in antifouling performance under static conditions, this study introduces a silicone-based antifouling coating modified with zwitterionic polymers. Sulfobetaine (SB) zwitterionic segments were grafted onto the side chains of poly(dimethylsiloxane) (PDMS) to synthesize the amphiphilic polymer P(DMS-SB), which was incorporated into the PDMS network to create an interpenetrating network-structured silicone coating. The zwitterionic segments effectively inhibited the adhesion of proteins, bacteria, and algae through hydration effects. Compared to pure PDMS coatings, the adhesion of proteins, bacteria, and algae was reduced by 88%, 98.9%, and 99.3%, respectively. Additionally, the coating demonstrated excellent fouling-release properties, achieving a 91.3% removal rate for settled algae under water flow conditions and reducing the simulated barnacle adhesion strength by 68.4%. This coating presents a promising antifouling solution for ships, offshore structures, and aquaculture facilities in static marine environments with significant potential for widespread application